Avaliação in situ do manchamento por café durante o período de remineralização do esmalte dentário de dentes clareados pela técnica de consultório - Mori, Aline Akemi (2011)
Objective: to evaluate the staining of coffee during the remineralization of tooth enamel by the in-office bleaching technique. Methods: Four volunteers used intraoral devices during two weeks containing dental nine blocks. Thirty-six specimens obtained from human teeth were randomly divided into 3 groups (n = 12), and each device contained three specimens of each group. The specimens already in position, were bleached with hydrogen peroxide gel 35% (Lase Peroxide Sensy ®, DMC, Brazil) in two sessions with an interval of three days in each session being held three applications of the gel for 20 minutes. In group 1 the specimens did not come into contact with the solution of coffee at any time (control group). In group 2 volunteers begun to enamel staining a week after the bleaching treatment. In group 3 volunteers began the process of staining the enamel immediately after bleaching of specimens. The staining was daily by immersing the surface in enamel specimens for 30 minutes in a solution of coffee color evaluation was performed with a spectrophotometer Easyshade ® (L * and ΔE) and the evaluation progressive mineralization of enamel in contact with saliva was performed using the DIAGNOdent® Laser Fluorescent. The evaluations of color and demineralization occurred in four moments: T1-Initial (before the treatment), T2, immediately after bleaching, T3-7 days after bleaching, and T4-14 days after bleaching. We conducted analysis of variance for repeated measures and Tukey's test (p <0.01) the variable mineralization and linear mixed effects model (p <0.05) for color evaluation. Results: The use of hydrogen peroxide bleaching promoted 35% of all specimens, there was significant difference in color in L * and ΔE between groups 1 and 3 in T1 (p <0.05) There was no statistical difference between the experimental and control groups for evaluation of color (L * and ΔE) on the measurements taken after bleaching. There was bleached enamel demineralization (T2) which after two weeks of bleaching treatment and contact with the saliva was not able to totally reverse the effects caused by hydrogen peroxide. Conclusions: Early contact (G3) or late (G2) with the solution of coffee did not cause significant change in the color of bleached teeth for the evaluation of ΔE, was higher enamel demineralization of the specimens after the sessions of whitening that at the end of 14 days of completion of treatment. Although the contact of specimens with saliva for 14 days has increased the degree of mineralization of enamel, the observed values did not return to its initial default, no correlation between enamel demineralization caused by hydrogen peroxide and the staining of enamel by the coffee solution according to the values of ΔE.